2019
DOI: 10.1074/jbc.ra119.009471
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of intermediates in the SufS cysteine desulfurase reaction reveals functional roles of conserved active-site residues

Abstract: Iron-sulfur (Fe-S) clusters are necessary for the proper functioning of numerous metalloproteins. Fe-S cluster (Isc) and sulfur utilization factor (Suf) pathways are the key biosynthetic routes responsible for generating these Fe-S cluster prosthetic groups in Escherichia coli. Although Isc dominates under normal conditions, Suf takes over during periods of iron depletion and oxidative stress. Sulfur acquisition via these systems relies on the ability to remove sulfur from free cysteine using a cysteine desulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 44 publications
6
39
0
Order By: Relevance
“…These interactions, especially found between the conserved His and the thiol group of PLP-L-cysteine, are beneficial for a nucleophilic attack to the thiol group of PLP-L-cysteine ketimine, which is converted from the corresponding aldimine, by the catalytic cysteine on the loop. The finding of interaction between the His and the thiol group in the present study is consistent with the results of the observation of the interaction in PLP-L-cysteine ketimine of the SufS variant in a recent study [20]. It should be noted that the PLP-L-cysteine and PLP-L-alanine aldimines in both NifS (type I) and SufS (type II) are in almost the same conformations with key interactions between the conserved histidine residues and the thiol groups.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…These interactions, especially found between the conserved His and the thiol group of PLP-L-cysteine, are beneficial for a nucleophilic attack to the thiol group of PLP-L-cysteine ketimine, which is converted from the corresponding aldimine, by the catalytic cysteine on the loop. The finding of interaction between the His and the thiol group in the present study is consistent with the results of the observation of the interaction in PLP-L-cysteine ketimine of the SufS variant in a recent study [20]. It should be noted that the PLP-L-cysteine and PLP-L-alanine aldimines in both NifS (type I) and SufS (type II) are in almost the same conformations with key interactions between the conserved histidine residues and the thiol groups.…”
Section: Introductionsupporting
confidence: 93%
“…The observed key interactions (e.g., interaction of conserved His-thiol group of PLP-L-cysteine) allowed to confirm the revised reaction mechanism (summarized in Fig. 9, including His-thiol interaction and difference of the loop motions in type I and II enzymes), which has also recently been demonstrated with X-ray crystallography on SufS variants and stopped-flow analysis by Outten et al [20]. Moreover, the intermediates were found in the identical conformations in both type I and type II, which indicated that the cysteine desulfurase enzymes commonly use the same intermediates based on PLP.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…2C). Recently, it has been found that H123 of E. coli SufS is required for CDS activity and that it may function as an acid-base catalyst in this mechanism (57). Moreover, the authors believed that H123 could deprotonate the catalytic thiol of C364 and share a π-π stacking interaction with PLP (57).…”
Section: Discussionmentioning
confidence: 99%